Pengaruh Gaya Hidup, Fasilitas, dan Kenyamanan Lingkungan Coffee Shop terhadap Minat Berkunjung Generasi Z di Kota Solo - Putri Anjarwati; Aditya Liliyan (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2026)
The expansion of the coffee sector in Solo has spurred fierce rivalry, notably in engaging the Generation Z demographic, who utilize coffee shops as platforms for both socializing and working. This research seeks to examine how lifestyle, facility availability, and environmental comfort impact the visiting intentions of Generation Z in Solo. Utilizing a quantitative method, data was gathered from 80 participants via purposive sampling. The data was processed through multiple linear regression using SPSS. Results indicate that, as a group, the three independent factors significantly affect visiting interest, accounting for 62.2% of the variance (Adjusted R Square). Individually, facilities (X2) and environmental comfort (X3) demonstrated positive and significant impacts, with facilities emerging as the primary driver. However, lifestyle (X1) did not significantly influence visiting intentions. This suggests that for Gen Z in Solo, functional utility and shop ambiance are more vital than mere social trends. Managers are encouraged to prioritize productivity-oriented facilities and spatial aesthetics to foster customer loyalty.